Development of a Popular Science Book on the Population Structure of Kapok (Ceiba pentandra Gaertn.) along the Banks of the Aluh Aluh River, Simpang Warga Village, Banjar District, South Kalimantan - Wulandari; Dharmono, Dharmono; Nurtamara, Luthfiana (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2024)
Teaching materials are a collection of books containing information or materials that are arranged in an orderly manner to support the learning process. The kapok plant found on the banks of the Aluh Aluh River, Simpang Warga Village, Banjar Regency, South Kalimantan, has the potential to be a source of learning based on local potential in the form of popular scientific books. This study aims to determine the population structure of kapok plants and determine the feasibility of popular scientific books on the structure of kapok populations as teaching materials for plant ecology. The method used is the 3-phase Plomp development method, namely preliminary research, prototype making phase, and assessment phase. The teaching materials in the form of popular scientific books that were developed have a validity score with very valid criteria and have a student readability score with very good criteria. So it can be concluded that the teaching materials of popular scientific books on the structure of kapok plant populations can be used as teaching materials in the learning process.